2017
DOI: 10.1186/s12984-017-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

Classification of upper limb center-out reaching tasks by means of EEG-based continuous decoding techniques

Abstract: BackgroundOne of the current challenges in brain-machine interfacing is to characterize and decode upper limb kinematics from brain signals, e.g. to control a prosthetic device. Recent research work states that it is possible to do so based on low frequency EEG components. However, the validity of these results is still a matter of discussion. In this paper, we assess the feasibility of decoding upper limb kinematics from EEG signals in center-out reaching tasks during passive and active movements.MethodsThe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 39 publications
(44 reference statements)
2
60
0
Order By: Relevance
“…The relationship of movement between the carriage and the motor revolutions is obtained from Equation (1). 21 The Direct Current (DC) motor that drives the gear system has a nominal supply voltage of 12 V and in nominal operation can vertically raise 3 kg (as measured on the guide carriage). This motor has a coupled reducer and an incremental encoder.…”
Section: Rehabilitation Guidementioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of movement between the carriage and the motor revolutions is obtained from Equation (1). 21 The Direct Current (DC) motor that drives the gear system has a nominal supply voltage of 12 V and in nominal operation can vertically raise 3 kg (as measured on the guide carriage). This motor has a coupled reducer and an incremental encoder.…”
Section: Rehabilitation Guidementioning
confidence: 99%
“…BCI technology can also be used to assist in rehabilitation, since BCIs aim to translate the patient's MI into external commands to control a helping device. The thought or realization of a motor action is generated in the sensory-motor areas of the cerebral cortex, which causes a variation in the EEG signal [21]. Specifically, imagining motor actions usually modifies the amplitude of the mu/beta rhythms in the sensory-motor cortex [22].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the low gamma (28-40 Hz) band could improve decoding accuracy for participants. Ubeda et al [29] confirmed the feasibility of decoding upper limb kinematics from EEG in center-out reaching tasks during passive and active movements. They applied the multidimensional linear regression model with kinematics state (position and velocity).…”
Section: Introductionmentioning
confidence: 92%
“…In these studies, kinematic parameters were directly decoded from the activity of larger regions of the scalp by applying linear decoders to SCPs for decoding both upper and lower limb joint movements (Bradberry et al, 2010 ; Presacco et al, 2011 ), sitting and standing states (Bulea et al, 2014 ), finger movements (Paek et al, 2014 ), and types of grasping (Agashe et al, 2015 ). Other studies have dealt with the characteristics of the performed movement, showing that hand kinematics are better decoded when continuous and linear movements are performed (Úbeda et al, 2015 ) and exploring the possibility of using them to classify reaching directions (Úbeda et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%